Risk Management on Infrastructure Projects and their Impact on Project Financials - Sitanggang, Oktavianus; Alam, Syamsul; ., Arifuddin; Aswan, Andi (Journal of Ecohumanism, 2025)
Purpose – This study aims to identify potential risks in infrastructure projects and determine their impact on project costs. The research addresses the financial implications of risk management practices in infrastructure development projects in Indonesia, focusing on operational, political, managerial, and technical risks. Design/methodology/approach – The research employs a mixed-method approach, integrating qualitative and quantitative methodologies. Data collection was conducted using questionnaires and semi-structured interviews to describe and verify the study findings. Additionally, the snowball sampling method was applied to gather data from Indonesian engineers working on infrastructure projects with contractors or consultants. Qualitative data was sourced from a comprehensive review of scientific literature related to risk management. Findings – Based on a survey of 50 construction practitioners, the study finds that infrastructure projects are highly likely to encounter multiple risks. Among these, the risk of principal insolvency has the most significant impact on infrastructure project costs, with an RII score of 3.04. Empirical findings reveal that only seven risk categories, including building structure risks, complaint and protest risks, contractual risks, approval risks, risks arising from service changes, maintenance risks, and vandalism risks, do not significantly affect infrastructure project costs in Indonesia. These risks can be managed through comprehensive project planning, clear contractual documentation specifying standards and specifications, and the inclusion of adjustment clauses. However, 16 other risk categories significantly impact project costs in the Indonesian infrastructure sector. Originality/value – This study extends the research by Fischer et al. (2010) by empirically testing risk categories to assess their impact on project costs. It adopts both quantitative and qualitative research approaches, focusing on the implementation practices of construction contractors within established project risk management frameworks. Practical implications – The findings provide actionable insights for policymakers, standardization boards, and construction practitioners, offering an empirical foundation for developing integrated and standardized risk management systems. These systems aim to enhance transparency and credibility by providing step-by-step instructions for interconnected subprocesses within the overall structure, improving information dissemination and decision-making accuracy.